The effect of bee pollen on reproductive and biochemical parameters in methotrexate-induced testicular damage in adult rats - Saral, Ozlem; Dokumacioglu, Eda; Saral, Sinan; Sumer, Aysegul; Bulmus, Ozgur; Kaya, Seyma Ozer; Canpolat, Sinan (De Gruyter Open Ltd, 2021)
Objectives: Methotrexate (MTX) is an anticancer drug used in chemotherapy. MTX was known for its toxic effects involving most of the organs including testis. Bee pollen is healthy food for human and has antioxidant effect. We intended to determine protective effect of bee pollen against testicular injury caused by MTX in rats. Methods: Thirty-two adult Sprague Dawley male rats were used, and 4 groups were formed: control, MTX, pollen, and MTX + pollen. Rats were given pollen at a dose of 400 mg/kg with intragastric gavage for 10 days. On day 7, MTX was administered a single dose of 30 mg/kg ip. Serum testosterone and LH, tissue MDA level, and SOD and CAT enzyme activities were examined. In addition, spermatological parameters were evaluated. Results: MDA level and SOD activity increased while testosterone level decreased significantly in the MTX group compared to the control group. In the MTX + pollen group, MDA level and SOD activity decreased while testosterone level increased. There was no significant change in CAT activity and LH values. Abnormal sperm ratio decreased in the MTX + pollen group compared to the MTX group. Conclusions: Our results suggest that bee pollen has a healing effect on reproductive parameters in testicular damage caused by MTX. © 2020 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: methotrexate; oxidative stress; pollen; testicular damage; testosterone